THE STUDY OF REBON SHRIMP PASTE (Acetes erythraeus) QUALITY WITH THE ADDITION OF DIFFERENT AMOUNT OF SALT - Andri Juwira Anwar; Sukirno Mus; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ASBTRACT The research was aimed to find out the effect of salt addition with different amount to the quality of rebonshrimp paste by looking at organoleptic and proximate values. The method used was an experimental method, with a Completely Randomized Design (CRD) which consists of 3 levels of treatment: 5g of salt (A1), 10g of salt (A2) and 12.5 g of salt (A3). The tested parameters were organoleptic (taste, aroma, consistency, and appearance) and proximate quality (water content, ash content, protein content, pH and fat content). The result of research based on organoleptic and chemical testshowed that the addition 10 g of salt was the best treatment, with taste 6.39 (shrimp taste slightly reduced, less salty), aroma 5.59 (the aroma of small shrimp paste was lacking), concistency 6.39 (thick, homogenous, and soft), appearance 6.63 (darkish brown tends to dull),while the water content28.10%, ash 3.05%, protein 8.78%, pH 7.05, and fat 0.68%. Keywords: small shrimp paste, addition of salt, organoleptic, proximate